2017
DOI: 10.1039/c7nh00024c
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial Ag–base metal nanowire networks with high electrochemical stability for transparent and stretchable asymmetric supercapacitors

Abstract: Based on electrochemically stable Ag–Ni and Ag–Fe core–shell nanowire networks, a transparent and stretchable asymmetric supercapacitor was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 47 publications
0
53
0
Order By: Relevance
“…Reproduced with permission. [47] Copyright 2017, Royal Society of Chemistry. Reproduced with permission.…”
Section: Graphene-based Stecmentioning
confidence: 99%
See 4 more Smart Citations
“…Reproduced with permission. [47] Copyright 2017, Royal Society of Chemistry. Reproduced with permission.…”
Section: Graphene-based Stecmentioning
confidence: 99%
“…[85] Furthermore, our group synthesized Ag@Ni core-shell structures and found that percolated Ag@Ni NW networks showed reversible stretchability and good electrochemical stability in stretchable transparent supercapacitors. [47] Therefore, further ongoing effort is necessary to develop the highly stable Ag NW-based STECs for various soft energy device applications.…”
Section: Metal Nw-based Stecmentioning
confidence: 99%
See 3 more Smart Citations